PENYULUHAN HUKUM PENGGUNAAN SOCIAL MEDIA YANG SESUAI DENGAN PERATURAN PERUNDANG-UNDANGAN BAGI SISWA SMA PELANGI KASIH - Ade Adhari; Joshua Steven Ongara; Ibra Fulenzi Amri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
Advances in information technology have led to the development of increasingly sophisticated and futuristic communication instruments and devices, notably the emergence of social media. Platforms such as Facebook, X, Instagram, TikTok, and similar services have become integral to human activity. Undeniably, the use of social media offers considerable convenience; however, it also has the potential to foster new behaviors within society that can bring both positive and negative consequences for individuals and users alike. Behaviors leading to negative outcomes can potentially result in criminal offenses, particularly among adolescents and students who may still struggle with emotional control. This article details a Community Engagement Program (PKM) conducted at SMA Pelangi Kasih, titled